Gaya Belajar Gaya Belajar Pendukung Ketuntasan Materi Hidrokarbon Aromatis dengan Model Perkuliahan Berdasarkan Masalah - Rinaningsih Rinaningsih; Tukiran Tukiran (Jurnal Penelitian Pendidikan IPA, 2024)
The characteristics of problem based learning are: problem posing; focuses on the interrelationships between disciplines; existence of authentic investigations; produce works and exhibit them; and cooperation in groups. The purpose of the research presentation in this article is to discuss learning styles supporting the mastery of Aromatic Hydrocarbons material with the Problem Based Learning Model. The results of the study found that the learning styles of mathematical logic, interpersonal, and intrapersonal support the mastery of Aromatic Hydrocarbons material. Study completeness in lectures on Aromatic Hydrocarbons material of 24% was achieved by students with very good criteria. The results of the presentation of research data can be concluded that learning styles with the same characteristics with problem based learning model can improve student learning outcomes.